Distinct and overlapping DNMT1 interactions with multiple transcription factors in erythroid cells: Evidence for co-repressor functions - Papageorgiou, Dimitris N; Karkoulia, Elena; Amaral-Psarris, Alexandra; Burda, Pavel; Kolodziej, Katarzyna; Demmers, Jeroen; Bungert, Jörg; Stopka, Tomas; Strouboulis, John (Biochimica et biophysica acta, 2016)
DNMT1 is the maintenance DNA methyltransferase shown to be essential for embryonic development and cellular growth and differentiation in many somatic tissues in mammals. Increasing evidence has also suggested a role for DNMT1 in repressing gene expression through interactions with specific transcription factors. Previously, we identified DNMT1 as an interacting partner of the TR2/TR4 nuclear receptor heterodimer in erythroid cells, implicated in the developmental silencing of fetal β-type globin genes in the adult stage of human erythropoiesis. Here, we extended this work by using a biotinylation tagging approach to characterize DNMT1 protein complexes in mouse erythroleukemic cells. We identified novel DNMT1 interactions with several hematopoietic transcription factors with essential roles in erythroid differentiation, including GATA1, GFI-1b and FOG-1. We provide evidence for DNMT1 forming distinct protein subcomplexes with specific transcription factors and propose the existence of a "core" DNMT1 complex with the transcription factors ZBP-89 and ZNF143, which is also present in non-hematopoietic cells. Furthermore, we identified the short (17a.a.) PCNA Binding Domain (PBD) located near the N-terminus of DNMT1 as being necessary for mediating interactions with the transcription factors described herein. Lastly, we provide evidence for DNMT1 serving as a co-repressor of ZBP-89 and GATA1 acting through upstream regulatory elements of the PU.1 and GATA1 gene loci.
Keywords: DNA vazebné proteiny; Erythropoiesis; Animals; Nuclear Proteins; trans-aktivátory; Repressor Proteins; erytroidní buňky; jaderné proteiny; transkripční faktory; represorové proteiny; Trans-Activators; vazba proteinů; Epigenetics; DNA-(cytosin-5)-methyltransferasa 1; buněčná diferenciace; lidé; Erythroid Cells; Mice; Transcription factors; Transcription Factors; protoonkogenní proteiny; metylace DNA; myši; Humans; DNA-(cytosin-5-)methyltransferasa; regulace genové exprese; DNA (Cytosine-5-)-Methyltransferases; DNA (Cytosine-5-)-Methyltransferase 1; DNA Methylation; DNMT1; Multiprotein Complexes; Proto-Oncogene Proteins; DNA-Binding Proteins; GATA1 Transcription Factor; Cell Differentiation; Gene Expression Regulation; zvířata; transkripční faktor GATA1; Protein Binding; multiproteinové komplexy